Postoperative High-Sensitivity Troponin and Its Association With 30-Day and 12-Month, All-Cause Mortality in Patients Undergoing On-Pump Cardiac Surgery. (October 2017) - Mauermann, Eckhard; Bolliger, Daniel; Fassl, Jens; Grapow, Martin; Seeberger, Esther E.; Seeberger, Manfred D.; Filipovic, Miodrag; Lurati Buse, Giovanna A. L.
Abstract : BACKGROUND: Troponin T is a predictor of cardiac morbidity and mortality after cardiac surgery with most data examining fourth generational troponin T assays. We hypothesize that postoperative high-sensitivity troponin T (hsTnT) measured in increments of the upper limit of the norm independently predicts 30-day all-cause mortality. METHODS: We included consecutive patients undergoing on-pump cardiac surgery from February 2010 to March 2012 in a prospective cohort that measured hsTnT at 0600 of the first and second postoperative day. Our primary end point was 30-day, all-cause mortality. The secondary end point was 12-month, all-cause mortality in patients surviving the first 30 days. We divided hsTnT into 5 predetermined categorizes based on the upper limit of the norm (ULN). We used Cox regression to examine an association of hsTnT independent of the EuroSCORE II at both 30 days as well as at 12 months in patients surviving the first 30 days. We assessed the area under the receiver operating characteristics curve and the net reassignment improvement for examining the benefit of adding of hsTnT to the EuroSCORE II for prognostication and restratification of 30-day, all-cause mortality. RESULTS: We included 1122 of 1155 eligible patients (75% male; mean age 66 ± 11 years). We observed 58 (5.2%) deaths at 30 days and another 35 (3.4%) deaths at 12 months in patients surviving 30 days. HsTnT categorized by ULN exhibited a graded response for the mortality. Furthermore, hsTnT remained an independent predictor of all-cause mortality at 30 days (adjusted hazard ratio 1.019 [1.014–1.024] per 10-fold increase in ULN) as well as at 12 months (adjusted hazard ratio 1.019 [1.007–1.032]) in patients surviving the first 30 days. The addition of hsTnT to the EuroSCORE II significantly increased the area under the receiver operating characteristics curve (area under curve: 0.816 [95% confidence interval, 0.754–0.878] versus area under curve: 0.870 [95% confidence interval, 0.822–0.917], respectively; P = .012). Finally, adding hsTnT to the EuroSCORE II improved restratification by the net reassignment improvement, primarily by improving rule-out of events. CONCLUSIONS: This analysis suggests that, similar to previous assays, higher postoperative concentrations of hsTnT are independently associated with all-cause mortality in patients undergoing on-pump cardiac surgery. Abstract : Supplemental Digital Content is available in the text.Published ahead of print May 19, 2017.